XRD RAMAN AND Uv-vis SPECTROSCOPICAL ANALYSIS OF NANOSTRUCTURED CdS:Li FILMS - Tülay Hurma (Anadolu University Journal of Science and Technology. A : Applied Sciences and Engineering, 2018)
CdS and CdS:Li films were produced my means of ultrasonic spray pyrolysis (USP) method by spraying on glass bases heated up to 340±5 ◦C. LiCl in three different rates was added into the preliminary solution while producing CdS:Li films. The effect of Li on the structural and optical characteristics of the CdS film was analyzed. XDR spectra showed that the crystallization degree decreases while lithium is 15% and increases when lithium rate increases. The crystallite sizes were calculated to be in the range of 60-85 nm. SEM photographs showed that the contribution of Li changed surface appearances of films and particle size. All films exhibit the Raman peaks centered 298 and 590 cm-1 and the peak profiles are almost symmetric. The optical band gap and Urbach energy values of these films were determined. The maximum transmittance is found to be almost 80% for the visible region. LiCl which was added to the preliminary solution changed the optical characteristics of CdS film.